2010
DOI: 10.2337/db10-0110
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Lipid and Protein Autacoids in Diabetic Vitreous Correlates With the Progression of Diabetic Retinopathy

Abstract: OBJECTIVEThis study was aimed at obtaining a profile of lipids and proteins with a paracrine function in normal and diabetic vitreous and exploring whether the profile correlates with retinal pathology.RESEARCH DESIGN AND METHODSVitreous was recovered from 47 individuals undergoing vitreoretinal surgery: 16 had nonproliferative diabetic retinopathy (NPDR), 15 had proliferative diabetic retinopathy, 7 had retinal detachments, and 9 had epiretinal membranes. Protein and lipid autacoid profiles were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 38 publications
(52 reference statements)
3
56
0
Order By: Relevance
“…5e8 Numerous studies have linked the overexpression of proinflammatory factors as an underlying cause of lowgrade inflammation. 5,9,10 Among these factors, the IL-1 subfamily of cytokines, consisting IL-1a, IL-1b, and IL-1 receptor antagonist (IL-1Ra, encoded by gene IL1RN in the humans), have attracted much attention because they have been implicated as a cause for the pathoencodesis of both type 1 11,12 and type 2 diabetes 13 and linked to complications with low-grade inflammation as a root cause. 8,14 IL-1 type cytokines are major mediators of inflammatory and innate immune reactions, and blockade of IL-1a and IL-1b by IL-1Ra has demonstrated a central role of IL-1 in several human autoinflammatory diseases, including rheumatoid arthritis and gout, and autoinflammatory syndromes.…”
mentioning
confidence: 99%
“…5e8 Numerous studies have linked the overexpression of proinflammatory factors as an underlying cause of lowgrade inflammation. 5,9,10 Among these factors, the IL-1 subfamily of cytokines, consisting IL-1a, IL-1b, and IL-1 receptor antagonist (IL-1Ra, encoded by gene IL1RN in the humans), have attracted much attention because they have been implicated as a cause for the pathoencodesis of both type 1 11,12 and type 2 diabetes 13 and linked to complications with low-grade inflammation as a root cause. 8,14 IL-1 type cytokines are major mediators of inflammatory and innate immune reactions, and blockade of IL-1a and IL-1b by IL-1Ra has demonstrated a central role of IL-1 in several human autoinflammatory diseases, including rheumatoid arthritis and gout, and autoinflammatory syndromes.…”
mentioning
confidence: 99%
“…64 As disease progresses, angiogenic factors that induce the growth of new retinal blood vessels (neovascularization) are secreted. 65 Yokoi et al 66 found that the vitreous levels of AGEs and vascular endothelial growth factor (VEGF) correlate with each other, both of which are inversely associated with vitreous total antioxidant capacity in patients with DR. Kinnunen et al 67 showed differences in growth factor expression between people with type 1 and type 2 DM with retinopathy, while VEGF-A was most abundantly present in type 1 DM, and VEGF-D was more copious in the neovascular tissues of patients with type 2 DM. They suggested the possibility that an inflammatory mechanism accelerates proliferative retinopathy in type 2, by VEGF-D-dependent pathways, and type 1 DM hypoxia is more important in the development of proliferative retinopathy than inflammation.…”
Section: Vitreousmentioning
confidence: 99%
“…2. 'Omics' studies, including proteomics [27,28] and lipidomics [29], which are beginning to be applied to diabetic retinopathy.…”
Section: Types Of Biomarkersmentioning
confidence: 99%